Traumatic orbital encephalocele: Presentation and imaging. (3rd March 2016) - Wei, Leslie A.; Kennedy, Tabassum A.; Paul, Sean; Wells, Timothy S.; Griepentrog, Greg J.; Lucarelli, Mark J.
ABSTRACT: Objective : Traumatic orbital encephalocele is a rare but severe complication of orbital roof fractures. We describe 3 cases of orbital encephalocele due to trauma in children. Methods : Retrospective case series from the University of Wisconsin – Madison and Medical College of Wisconsin. Results : Three cases of traumatic orbital encephalocele in pediatric patients were found. The mechanism of injury was motor vehicle accident in 2 patients and accidental self-inflicted gunshot wound in 1 patient. All 3 patients sustained orbital roof fractures (4 mm to 19 mm in width) and frontal lobe contusions with high intracranial pressure. A key finding in all 3 cases was progression of proptosis and globe displacement 4 to 11 days after initial injury. On initial CT, all were diagnosed with extraconal hemorrhage adjacent to the roof fractures, with subsequent enlargement of the mass and eventual diagnosis of encephalocele. Conclusion : Orbital encephalocele is a severe and sight-threatening complication of orbital roof fractures. Post-traumatic orbital encephalocele can be challenging to diagnose on CT as patients with this condition often have associated orbital and intracranial hematoma, which can be difficult to distinguish from herniated brain tissue. When there is a high index of suspicion for encephalocele, an MRI of the orbits and brain with contrast should be obtained for additional characterization. Imaging signs that should raise suspicion for traumatic orbital encephalocele include an enlarging heterogeneous orbital mass in conjunction with a roof fracture and/or widening fracture segments.